2004
DOI: 10.3317/jraas.2004.037
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulates arachidonic acid release from bone marrow stromal cells

Abstract: Introduction Angiotensin II (Ang II) is recognised as a regulator of haematopoiesis, but its actions within the bone marrow are not fully understood. Support of haematopoiesis by bone marrow stromal cells (MSC) is dependent on factors that include arachidonic acid and macrophage colony stimulating factor (MCSF), both of which are increased by Ang II stimulation in other tissues. To further elucidate the mechanisms of Ang II-regulated haematopoiesis, we determined whether Ang II-stimulation alters arachidonic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 50 publications
(66 reference statements)
0
20
1
Order By: Relevance
“…It is known that these two receptors are expressed in the monkey and human HS-5 stromal cell line at the protein level [27]. Nevertheless, AT2R mRNA was not detected in human MSCs [27]. However, our study detected not only AT1R mRNA but also AT2R mRNA in cultured human bone marrow MSCs.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…It is known that these two receptors are expressed in the monkey and human HS-5 stromal cell line at the protein level [27]. Nevertheless, AT2R mRNA was not detected in human MSCs [27]. However, our study detected not only AT1R mRNA but also AT2R mRNA in cultured human bone marrow MSCs.…”
Section: Discussioncontrasting
confidence: 50%
“…It is known that these two receptors are expressed in the monkey and human HS-5 stromal cell line at the protein level [27]. Nevertheless, AT2R mRNA was not detected in human MSCs [27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ang II has been shown to trigger arachidonic acid release from bone marrow cells via AT 1 and AT 2 receptor–mediated pathways. 36 We, therefore, quantitated urinary excretion of prostaglandin E 2 and prostacyclin by ELISA in the Ang II-infused BMWT and BMKO groups (n=14 per group). We found that urinary prostaglandin E 2 (2663±297 versus 2988±404 pg per 24 hours; P value not significant) and prostacyclin (10 321 ±1177 versus 11 643±2097 pg per 24 hours; P value not significant) were similar in the BMWT and BMKO groups, suggesting that differential generation of vasodilatory prostaglandins did not contribute to the enhanced blood pressure elevation in the Ang II-infused BMKO group.…”
Section: Resultsmentioning
confidence: 99%
“…These studies suggest a fundamental role of AT 1 receptor activation in atherogenesis 31. In the pursuit of the mechanism accounting for the actions of Ang II in atherogenesis, we found that early activation of monocytes occurred through upregulation of the bone marrow renin-angiotensin system, whereby hypercholesterolemia stimulates the expression of bone marrow CD11b (+) receptors in monocytes 3234…”
Section: Role Of the Renin-angiotensin-aldosterone System (Raas) In Ementioning
confidence: 96%